2014
DOI: 10.1186/1471-2407-14-486
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of HLA class I, HLA-E, HLA-G and Tregs in rectal cancer: a retrospective cohort study

Abstract: BackgroundEvasion of immune surveillance and suppression of the immune system are important hallmarks of tumorigenesis. The goal of this study was to establish distinct patterns that reflect a rectal tumors’ immune-phenotype and to determine their relation to patient outcome.MethodsThe study population consisted of 495 Stage I-IV non-preoperatively treated rectal cancer patients of which a tissue micro array (TMA) was available. Sections of this TMA were immunohistochemically stained and quantified for presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 54 publications
5
87
1
Order By: Relevance
“…In addition, increased HLA-E mRNA transcript levels in RCC lesions were associated with a worse prognosis of RCC patients [28] and thus might have a predictive value in tumor progression of this disease. This is in line with reports on breast and ovarian cancer, where HLA-G or HLA-E expression correlated with a worse overall and event-free survival [15] and also in rectal and colon cancers, in which a combination of the immune-related markers HLA class I, HLA-G, HLA-E and FoxP3 reflect an immune escape mechanism [29, 30]. Using qPCR, flow cytometry and/or immunohistochemistry (IHC) this study analyzed the expression of HLA-E in RCC cell lines as well as in RCC lesions and correlated these data with clinical and immunologic parameters.…”
Section: Introductionsupporting
confidence: 91%
“…In addition, increased HLA-E mRNA transcript levels in RCC lesions were associated with a worse prognosis of RCC patients [28] and thus might have a predictive value in tumor progression of this disease. This is in line with reports on breast and ovarian cancer, where HLA-G or HLA-E expression correlated with a worse overall and event-free survival [15] and also in rectal and colon cancers, in which a combination of the immune-related markers HLA class I, HLA-G, HLA-E and FoxP3 reflect an immune escape mechanism [29, 30]. Using qPCR, flow cytometry and/or immunohistochemistry (IHC) this study analyzed the expression of HLA-E in RCC cell lines as well as in RCC lesions and correlated these data with clinical and immunologic parameters.…”
Section: Introductionsupporting
confidence: 91%
“…Moreover, our results showed that the expression level of ERO1-a was significantly correlated with the expression of MHC class I. Because many studies have demonstrated that low MHC class I expression is associated with poor prognosis (25)(26)(27), we are currently investigating whether low expression of ERO1-a correlates with poor prognosis. In conclusion, the cancer-associated ERO1-a plays a pivotal role in the host's immune response via proper Ag presentation by MHC class I molecules within a hypoxic microenvironment.…”
Section: Discussionmentioning
confidence: 70%
“…2016 (42) FCM, flow cytometry; ELISA, enzyme-linked immunosorbent assay; IHC, immunohistochemistry in this study [88]. Recently, our group explored HLA-G expression in patients with H. pylori infection and gastric cancer.…”
Section: (41)mentioning
confidence: 99%